Islamic Economic Principles in Healthcare: Analyzing the Impact on Islamic Hospitals through Bibliometrics - Apriantoro, Muhamad Subhi; Saifullah, Muhammad Fahmi (Invest Journal of Sharia & Economic Law, 2025)
This study explores the application of Islamic economic principles in healthcare, specifically through Islamic hospitals. Employing bibliometric analysis and network visualization techniques, data from the Scopus database revealed 722 articles published between 1973 and 2024 were analyzed. Tools such as Microsoft Excel, R/RStudio, and VOSviewer were used to analyze these documents and visualize a network of keywords that highlight the economic aspects of Islamic hospitals. The findings indicate a steady growth in publications at a rate of 7.03% annually, with 2019 marking the highest number. Iran has emerged as a significant contributor to this body of research, particularly through the Tehran University of Medical Sciences, while the Eastern Mediterranean Health Journal has served as the primary publication outlet. Keyword network analysis uncovered four main clusters: financing models, cost-effectiveness, resource allocation, and ethical considerations in healthcare. This study sheds light on the integration of Islamic economic principles in healthcare settings and lays the groundwork for future research on optimizing economic practices in Islamic hospitals.